Notifiche
Cancella tutti

Integrale

  

1
547

Spiegare e argomentare.

Autore
1 Risposta



2

(x - 1)^2 / x^2 = (x^2 + 1 - 2x) / x^2 = x^2 / x^2 + 1/x^2  - 2x/x^2 =

= 1 + 1/x^2 - 2/x;

∫[1 + (x^-2)  - 2/x] dx = 1 dx + (x^-2) dx - 2(1/x) dx; calcolato tra 1 e 2; 

= x + [x^-1/ (-1)] - 2 ln(x)  calcolato tra 1 e 2;

= x - 1/x - 2 ln(x) ;  calcolato tra 1 e 2;

= [2 - 1/2 - 2 ln(2)] - [1 - 1 - 2 ln(1)] = [4/2 -1/2 - 2 ln(2)] - [ 0 ] =

= 3/2 - 2 ln(2).

@alby   ciao.



Risposta
SOS Matematica

4.6
SCARICA